Dataset of the manuscript Electrocatalytic hydrogenation of unsaturated organics using Mo and W porous carbon-encapsulated nanostructures: impact of metal type on properties and performances - Pota, Filippo; Colavita, Paula; Costa de Oliveira, Maida; Rafferty, Aran (Trinity College Dublin, 2024)
The present dataset is composed of 6 different methods used for the measurements, characterizations, and analysis: 1) X-ray diffraction (XRD): This dataset includes raw measurements for RPM/BP, W@C:N, and Mo@C:N. Each material is represented by two columns: 2 teta (°) and Intensity (a.u.). 2) Brunauer–Emmett–Teller method (BET): This dataset contains raw measurements for isotherms and pore size distributions performed for RPM/BP, Mo@C:N, and W@C:N. 3) X-ray photoelectron spectroscopy (XPS): This dataset describes the elemental composition and distributions of each component (C, N, and Mo or W) for high-resolution measurements and the survey of carbon model electrodes. The files are composed of two columns, corresponding to the Intensity (a.u.) and Binding Energy (eV) plus each specific contribution. This data can be analyzed by CasaXPS software. 4) Scanning electron microscopy (SEM): This dataset cosists of word file containg raw spetrum and images of the mapping collected for Mo@C:N and W@C:N 5) Electrochemistry: This dataset describes the response of tested electrodes. Contains voltammetry (CV and LSV) and electrolysis raw data at differenct conditions of organic concetration and potential applied. It also contains calculated Faradic efficiency (FE), Product rate and Turn over frequency (TOF). 6) Transmission electron microscopy (TEM): this dataset contains images and EDX mapping reports collected for Fe@C:N
PUBLISHED